Advancing Sustainable Economic Empowerment in Pesantren by Community-Based Development Theory - Muiz, Abdul; Aini, Siti Qurratul; Noh , Mohd Shahid Bin Mohd (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
The sustainability of Pesantren is increasingly challenged by financial limitations, especially in rural areas where state support and institutional funding are minimal. This study examines the viability of ensuring pesantren sustainability through the empowerment of the people’s economy, framed by Community-Based Development Theory. As globally, educational institutions grapple with socioeconomic inequality and resource scarcity, this research offers a contextually grounded yet globally relevant model for faith-based community empowerment. Drawing on a case study of Al Hasan I Pesantren in Jember, Indonesia, the study explores how economic self-reliance initiatives—such as micro-enterprises, agricultural development, and vocational training—are integrated with religious education to build institutional resilience and local economic capacity. The novelty of this research lies in its interdisciplinary approach, combining Islamic economics with grassroots development theory to address both educational sustainability and economic justice. Findings reveal that pesantren can function as effective agents of social transformation by mobilizing community participation, Islamic ethical values, and economic innovation. This paper contributes to global discussions on alternative development strategies and offers a replicable model for similar institutions in Muslim-majority countries seeking sustainable pathways rooted in religious and communal principles.